Altered social decision making in patients with chronic pain. Issue 6 (5th April 2023) - Timm, Alicja; Schmidt-Wilcke, Tobias; Blenk, Sandra; Studer, Bettina
Abstract: Background: Chronic pain affects up to 20% of the population, impairs quality of life and reduces social participation. Previous research reported that pain-related perceived injustice covaries with these negative consequences. The current study probed whether chronic pain patients responded more strongly to disadvantageous social inequity than healthy individuals. Methods: We administered the Ultimatum Game, a neuroeconomic social exchange game, where a sum of money is split between two players to a large sample of patients with chronic pain disorder with somatic and psychological factors ( n = 102) and healthy controls ( n = 101). Anonymised, and in truth experimentally controlled, co-players proposed a split, and our participants either accepted or rejected these offers. Results: Chronic pain patients were hypersensitive to disadvantageous inequity and punished their co-players for proposed unequal splits more often than healthy controls. Furthermore, this systematic shift in social decision making was independent of patients' performance on tests of executive functions and risk-sensitive (non-social) decision making . Conclusions: Our findings indicate that chronic pain is associated with anomalies in social decision making (compared to healthy controls) and hypersensitivity to social inequity that is likely to negatively impact social partaking and thereby the quality of life.